Influence of the physico-chemical properties of root mucilage and model substances on the microstructural stability of sand - Brax, Mathilde; Buchmann, Christian; Kenngott, Kilian; Schaumann, Gabriele Ellen; Diehl, Dörte (Biogeochemistry, 2020)
Root mucilage (RM), a soil-born biohydrogel, affects the physical stability of the rhizosphere. One reason for this is attributed to the present polysaccharides which contribute to the formation of aggregates by acting as interparticulate glue. The aim of this study was to explore how physico-chemical properties of polymers of interparticulate gels influence this gluing and thus soil microstructural stability. We hypothesized that the microstructural stability of sand increases with the viscosity of the amended biohydrogel, which depends on the content of carbohydrate polymers and non-esterified uronic acids which themselves determine the amount of absorbed calcium. Therefore, natural RM of maize and wheat were compared with higher viscous chia seed mucilage (SM) as a widely used model for RM, and with industrial pectin rich in uronic acids partially methylated. Results show that additionally to Ca binding by uronic acids, binding by proteins is a further possible mechanism of Ca adsorption in RM. Upon Ca addition, the viscosity increased upon intermolecular associations (pectin) and decreased upon suppression of intermolecular charge–charge repulsion (chia SM, maize RM). Amount of high-molecular weight material in the amendment affected strongly soil microstructural stability. Results further suggest the creation of gel micro-zones upon Ca addition, which increase the viscosity of interparticulate gel and sand microstructural stability. Finally, the study outlines several physico-chemical mechanisms through which interactions between biotic (roots and seed) and abiotic components (mineral particles) influence soil structure, which control the water, air and nutrient flow through the rhizosphere and is, thus, an important soil quality parameter.